Perbandingan Konservatif Fisioterapi Dengan Core Stability Exercise Pada Kasus Nyeri Punggung Bawah - Pradita, Angria; Nurul Halimah (Jurnal Fisioterapi Terapan Indonesia, 2024)
ABSTRACT: Low back pain is a major complaint caused by multifactorial conditions. The most common factors of low back pain complaints are due to age, occupation and gender. This study aims to compare the differences in therapeutic effects of conservative physiotherapy with the provision of electrotherapy, namely; microwave diathermy combined with transcutaneous electrical nerve stimulation (TENS), core stability exercise techniques and a combination of electrotherapy with core stability exercise (CSE). This type of research is quasi experimental with a pre-post test design in a population of 90 low back pain patients who seek treatment at the Physiotherapy clinic. By using purposive sampling technique of 60 patients who have met the exclusion and inclusion criteria, patients were divided into intervention groups, namely; (1) conservative physiotherapy (electrotherapy); (2) core stability exercise; (3) conservative physiotherapy and core stability exercise. Data collection techniques using visual analogue scale (VAS) measurement, and schoober method with analysis test using krusskal wallis. The results of this study showed a difference in the median value of pain of 2 (group 1), 4 (group 2), and 3.5 (group 3) with a P value on pain of 0.06>0.05, and a difference in the median value of muscle flexibility of 1.5 (group 1); 1.75 (group 2); 1.75 (group 3) with a P value showing 0.895. The three intervention groups have no difference in reducing pain and increasing flexibility.